THE CHARACTERISTICS OF BREEDERS, MANAGEMENT PRACTICES, AND MARKETING EFFICIENCY OF BALI CALF CATTLE IN NUSA PENIDA, INDONESIA: A CASE STUDY - N. M. A. K., DEWI; PUTRI, B. R. T.; SUKANATA, I. W. (Majalah Ilmiah Peternakan, 2024)
This study analyzes the characteristics of Bali cattle breeders, management practices, and the marketing effi- ciency of Bali calves in Nusa Penida, Indonesia. Data from 60 breeders, 10 belantik (cattle traders), and 4 experts revealed a predominantly male-dominated sector with a high reliance on traditional, semi-intensive farming met- hods. Small-scale operations and limited market access, coupled with a long marketing chain involving belantik, significantly constrain profitability. Direct marketing, while less prevalent, demonstrates markedly higher efficien- cy and farmer’s share. The findings highlight the need for interventions to improve market access, enhance farming practices, and strengthen farmer organizations to ensure the long-term sustainability of this important sector.